Notch sensitivity jeopardizes titanium locking plate fatigue strength. Issue 12 (December 2016) - Tseng, Wo-Jan; Chao, Ching-Kong; Wang, Chun-Chin; Lin, Jinn
Abstract: Introduction: Notch sensitivity may compromise titanium-alloy plate fatigue strength. However, no studies providing head-to-head comparisons of stainless-steel or titanium-alloy locking plates exist. Materials and methods: Custom-designed identically structured locking plates were made from stainless steel (F138 and F1314) or titanium alloy. Three screw-hole designs were compared: threaded screw-holes with angle edges (type I); threaded screw-holes with chamfered edges (type II); and non-threaded screw-holes with chamfered edges (type III). The plates' bending stiffness, bending strength, and fatigue life, were investigated. The stress concentration at the screw threads was assessed using finite element analyses (FEA). Results: The titanium plates had higher bending strength than the F1314 and F138 plates (2.95:1.56:1) in static loading tests. For all metals, the type-III plate fatigue life was highest, followed by type-II and type-I. The type-III titanium plates had longer fatigue lives than their F138 counterparts, but the type-I and type-II titanium plates had significantly shorter fatigue lives. All F1314 plate types had longer fatigue lives than the type-III titanium plates. The FEA showed minimal stress difference (0.4%) between types II and III, but the stress for types II and III was lower (11.9% and 12.4%) than that for type I. Conclusions: The screw threads did not cause stress concentration in the locking plates in FEA, but may have jeopardized the fatigue strength, especially in the notch-sensitive titanium plates. Improvement to the locking plate design is necessary.